INCREASING KNOWLEDGE THROUGH COUNSELING ACTIVITIES ABOUT HIV/AIDS AT SMTK YAKBADO, DOGIYAI REGENCY - Joko Prasetyo; Isak Waine (Jurnal Abdisci, 2024)
Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) is one of the health problems in the world, including Indonesia. The number of HIV/AIDS cases continues to increase from year to year. HIV/AIDS is one of the deadly diseases that has not yet been found a cure, so innovation is needed to cure HIV/AIDS sufferers. Therefore, counseling needs to be carried out to prevent an increase in HIV/AIDS sufferers in the community. Counseling activities about HIV/AIDS were carried out on August 25, 2023, at SMTK Yakbado, Dogiyai Regency, using counseling and questionnaires in the form of Pre-Test and Post-Test in statistical tests. The results of the statistical test showed an increase in knowledge before and after counseling about HIV/AIDS from the results (pretest 6.30% and posttest 7.88%) from 28 students with ten questions.